2015
DOI: 10.1016/j.virol.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS1 protein interacts with the ribosomal protein RPL18: This interaction is required for viral translation and replication in Huh-7 cells

Abstract: Given dengue virus (DENV) genome austerity, it uses cellular molecules and structures for virion entry, translation and replication of the genome. NS1 is a multifunctional protein key to viral replication and pathogenesis. Identification of cellular proteins that interact with NS1 may help in further understanding the functions of NS1. In this paper we isolated a total of 64 proteins from DENV infected human hepatic cells (Huh-7) that interact with NS1 by affinity chromatography and immunoprecipitation assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 55 publications
3
54
0
Order By: Relevance
“…Second, DENV infection might limit the availability of the translation machinery components such as ribosomal subunits. Affinity purification and mass spectrometry analyses of DENV-infected cells revealed the interaction of NS1 with over 30 ribosomal proteins such as RPL18 which is required for both viral replication and translation (86). Third, our results indicate that viral replication is dispensable for the induction of translational repression, as illustrated by the absence of puromycin incorporation in single cells expressing DENV polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Second, DENV infection might limit the availability of the translation machinery components such as ribosomal subunits. Affinity purification and mass spectrometry analyses of DENV-infected cells revealed the interaction of NS1 with over 30 ribosomal proteins such as RPL18 which is required for both viral replication and translation (86). Third, our results indicate that viral replication is dispensable for the induction of translational repression, as illustrated by the absence of puromycin incorporation in single cells expressing DENV polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001; ****, P Ͻ 0.0001. DENV-2 infection without affecting global cellular translation or cell viability (52). RPS25 appears to be broadly required for IRES-mediated translation initiation of HCV, human T-cell leukemia virus 1, Cricket paralysis virus, and poliovirus, as well as ribosome shunting in adenovirus infection (21,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that N of Rice stripe tenuivirus interacts with RPL18 of insect vector and silencing of RPL18 significantly reduces viral translation and replication in insect vector [82]. Interaction between NS1 of Dengue virus (DENV) and RPL18 in human hepatic cells (Huh-7) exhibits a similar significance [83]. The above researches describe the upregulating role of RPL18 on virus translation.…”
Section: Interaction Between Viral Proteins and Ribosomal Proteinsmentioning
confidence: 90%